Analysis of The Role of Management Information Systems in The Decision Making Process at PT. Indonesian Trading Company Medan - Mukmin Pohan (AIBPM Publisher, 2021)
Every company will always be faced with uncertain situations that may support or hinder the company in achieving its goals. To be able to determine an attitude or take a decision in the face of a situation full of uncertainty, managers/managers need a variety of information. Good decisions can be made by managers at every level of management, if efficient, precise and direct information is available. How information is presented to managers depends on the merits of the management information system of the company. To discuss these problems, literature research and field research were carried out at PT. Indonesian Trading Company Medan. The results of research and discussion explain that a good management information system will have the ability to process data from all company activities into useful information and take over the management decision-making process. Although the supporting factors are adequate, there are still system errors and weaknesses in the design and implementation. These weaknesses are like processing data into information which takes a lot of time because information is processed in every part of the company so that it requires continuous supervision from the leaders. Information is distributed based on levels according to the organizational structure from superiors to subordinates. If circumstances force, the distribution of the information will no longer take place based on the level but directly to the superior, because the superior is obliged to make decisions that are exceptions to the problem.